A Study of Stakeholder Views to Shape a Communication Strategy for GMO in Brazil - Capalbo, Deise Maria Fontana; Arantes, Olivia Márcia Nagy; Maia, Alexandre Gori; Borges, Izaias Carvalho; Silveira, José Maria Ferreira Jardim da (Frontiers in Bioengineering and Biotechnology, 2015)
This paper analyzes the view of stakeholders on genetically modified organisms and the implications of these views on communication strategies for agricultural biotechnology in Brazil. It identifies and describes common groups of attitudes toward genetically modified organisms using multivariate statistical analyses. The study then looks for patterns of association between the common attitude groups and the following variables: socioeconomic characteristics trust in institutions as information sources and familiarity with the Brazilian biosafety authority. The article contributes to the understanding of public awareness by highlighting how information sources, trust in institutions, and socioeconomic characteristics, such as age and occupational qualification, play important roles in defining patterns of attitudes toward genetically modified organisms. The paper also discusses the implications of this knowledge for the development of a communication strategy plan that would promote public awareness and stimulate a well-informed Brazilian public debate on biosafety.